The Impact of EMU on Inflation Expectations - Friedrich Heinemann; Katrin Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper analyses the impact of the monetary regime change from the Bundesbank to the ECB in 1999 on inflation expectations. In the theoretical part, the Barro-Gordon model is used to derive the potential effect of a new central bank on inflation, inflation expectations and forecast errors. The econometric investigation is based on a flexible specification of expectation formation which allows both for rational and adaptive elements. Data on inflation expectations originate from the ZEW Financial Market Survey. The results indicate that the monetary regime change did not have a strong and lasting impact on the formation of inflation expectations and that the anti-inflationary credibility of both central banks is not perceived to differ significantly. However, the analysis also reveals that the years immediately before the start of EMU were characterised by a relatively large degree of uncertainty: in this time, market participants resorted to backward-looking expectations even more than usually. This is a plausible result because of the intitial uncertainty about the new central bank?s characteristics. Once in charge of monetary policy the ECB was quickly successful to restore certainty about its true Bundesbank-like type.
Keywords: E31; E58; 330; inflation expectations; credibility; ZEW Financial market survey; ECB; EMU; Carlson-Parkin; Inflationserwartung; Geldverfassung; Europäische Wirtschafts- und Währungsunion; Schätzung; Deutschland